การบริหารงานวิชาการตามหลักปัญญา 3 ของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาร้อยเอ็ด เขต 2 - พาตา, รพีพร; ผศ.ดร., พระครูวิจิตรปัญญาภรณ์ (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 4 No 2 (2567): พฤษภาคม – สิงหาคม 2567, 2023)
การวิจัยครั้งนี้มีวัตถุประสงค์ 1) เพื่อศึกษาสภาพปัจจุบัน สภาพที่พึงประสงค์และความต้องการจำเป็น ในการบริหารงานวิชาการตามหลักปัญญา 3 ของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาร้อยเอ็ด เขต 2 2) เพื่อศึกษาแนวทางในการบริหารงานการบริหารงานวิชาการตามหลักปัญญา 3 ของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาร้อยเอ็ด เขต 2 กลุ่มตัวอย่าง ได้แก่ ผู้บริหารและครูผู้สอน จำนวน 351 คน กลุ่มเป้าหมายเพื่อการสัมภาษณ์เป็นผู้บริหารและครู จำนวน 5 คน เครื่องมือที่ใช้ในการวิจัยเป็นแบบสอบถามแบบ สถิติที่ใช้ในการวิจัย ได้แก่ ความถี่ ร้อยละ ค่าเฉลี่ย  ส่วนเบี่ยงเบนมาตรฐาน และประเมินความต้องการจำเป็นด้วยค่า PNI modified และการวิเคราะห์เชิงพรรณนา ผลการวิจัยพบว่า 1) สภาพปัจจุบันการบริหารงานวิชาการตามหลักปัญญา 3 โดยภาพรวมอยู่ในระดับปานกลาง เมื่อพิจารณาเป็นรายด้าน เรียงลำดับจากสูงสุดไปต่ำสุด ได้แก่ ด้านการนิเทศการศึกษา รองลงมาคือ ด้านการวิจัยเพื่อพัฒนาคุณภาพการศึกษา ด้านการวัดผล ประเมินผลการเรียนรู้ ด้านการจัดการเรียนการสอนในสถานศึกษา ด้านสื่อนวัตกรรม เทคโนโลยีและแหล่งเรียนรู้ และด้านการพัฒนาหลักสูตรในสถานศึกษา สภาพที่พึงประสงค์การบริหารงานวิชาการตามหลักปัญญา 3 โดยภาพรวมอยู่ในระดับมาก เรียงลำดับจากสูงสุดไปต่ำสุด ได้แก่ ด้านการจัดการเรียนการสอนในสถานศึกษา ด้านการวัดผลประเมินผลการเรียนรู้ ด้านการนิเทศการศึกษา ด้านการวิจัยเพื่อพัฒนาคุณภาพการศึกษา ด้านสื่อ นวัตกรรม เทคโนโลยีและแหล่งเรียนรู้ และด้านการพัฒนาหลักสูตรในสถานศึกษา และความต้องการจำเป็น ได้แก่ (1) ด้านการจัดการเรียนการสอนในสถานศึกษา (2) ด้านการวัดผล ประเมินผลการเรียนรู้ (3) ด้านการพัฒนาหลักสูตรในสถานศึกษา (4) ด้านสื่อ นวัตกรรม เทคโนโลยีและแหล่งเรียนรู้ (5) ด้านการนิเทศการศึกษา (6) ด้านการวิจัยเพื่อพัฒนาคุณภาพการศึกษา 2) แนวทางการบริหารงานวิชาการตามหลักปัญญา 3 ผู้บริหารควรสร้างบริบทความเป็นวิชาการที่เป็นเลิศในสถานศึกษาอย่างเป็นรูปธรรม เน้นการใช้สื่อการเรียนการสอน ควรให้ความสำคัญกับการพัฒนาองค์รวมของมนุษย์ การเสนอมาตรการต่างๆ เพื่อแก้ไขปัญหาการศึกษา มาตรการเหล่านี้รวมถึงการให้ผู้มีส่วนได้ส่วนเสีย ครูควรเข้าถึงสื่อการสอนและแหล่งการเรียนรู้ที่เหมาะสมกับศักยภาพที่แท้จริงของผู้เรียน เพื่อพัฒนาคุณภาพการเรียนรู้ The objectives of this research were 1) to study the current situation, desirable conditions, and necessity requirements for academic administration based on wisdom 3 of educational institution administrators under Roi-Et Primary Educational Service Area Office 2, and 2) to study practical guidelines for academic administration based on wisdom 3 of educational institution administrators under Roi-Et Primary Educational Service Area Office 2. The sample group consisted of 351 Educational institution administrators and teachers, and the target group of 5 people for interviewing educational institution administrators and teachers. The research instrument was questionnaire. Statistics used were frequency, percentage, mean, and standard deviation. the necessities were assessed by PNI modified and descriptive analysis. The results showed that: 1) The current state of academic administration based on the Wisdom 3 overall was at a moderate level. The aspects can be ranked from highest to lowest as follows: educational administration, research for educational quality improvement, measurement and evaluation of learning outcomes, management of teaching and learning in schools, media innovation, technology and learning resources, and curriculum development in educational institutions. As for the desired state of academic administration based on the Wisdom 3, when considering each aspect ordered from the highest to the lowest, they were educational supervision, followed by research to improve the quality of education, measurement, assessment for learning, teaching and learning management in educational institutions, innovative media, technology and learning resources, and curriculum development in educational institutions. Desirable conditions for academic administrations based on wisdom 3 overall was at a high level considering each aspect ordered from the highest to the lowest: teaching and learning management in educational institutions, assessment for learning, educational supervision, research to improve the quality of education, innovative media, technology and learning resources, curriculum development in educational institutions, and necessities included: 1. Teaching and learning management in educational institutions 2. Assessment and evaluation for learning 3. Curriculum development in educational institutions 4. innovative media, technology and learning resources 5. educational supervision 6. research to improve the quality of education. 2) Academic administration guidelines based on the Wisdom 3: educational institutions should create a concrete context of academic excellence in educational institutions, emphasized on the use of teaching materials, should focus on the holistic development of human being, proposed measures to solve education problems included giving stakeholders, teachers should have access to teaching materials and learning resources that were appropriated to the true potential of learners for improving the quality of learning.